Delivery Mode After Manual Rotation of Occiput Posterior Fetal Positions: A Randomized Controlled Trial. Issue 6 (June 2021) - Verhaeghe, Caroline; Corroenne, Romain; Spiers, Andrew; Descamps, Philippe; Gascoin, Géraldine; Bouet, Pierre-Emmanuel; Parot-Schinkel, Elsa; Legendre, Guillaume
Abstract : OBJECTIVE: To evaluate whether manual rotation of fetuses in occiput posterior positions at full dilation increases the rate of spontaneous vaginal delivery. METHODS: In an open, single-center, randomized controlled trial, patients with a term, singleton gestation, epidural analgesia, and ultrasonogram-confirmed occiput posterior position at the start of the second stage of labor were randomized to either manual rotation or expectant management. Our primary endpoint was the rate of spontaneous vaginal delivery. Secondary endpoints were operative vaginal delivery, cesarean delivery, and maternal and neonatal morbidity. Analyses were based on an intention-to-treat method. A sample size of 107 patients per group (n=214) was planned to detect a 20% increase in the percent of patients with a spontaneous vaginal delivery (assuming 60% without manual rotation vs 80% with manual rotation) with 90% power and alpha of 0.05. RESULTS: Between February 2017 and January 2020, 236 patients were randomized to either manual rotation (n=117) or expectant management (n=119). The success rate of the manual rotation maneuver, defined by conversion to an anterior position as confirmed by ultrasonogram, was 68%. The rate of the primary endpoint did not differ between the groups (58.1% in manual rotation group vs 59.7% in expectant management group (risk difference −1.6; 95% CI −14.1 to 11.0). Manual rotation did not decrease the rate of operative vaginal delivery (29.9% in manual rotation group vs 33.6% in expectant management group (risk difference −3.7; 95% CI −16.6 to 8.2) nor the rate of cesarean delivery (12.0% in manual rotation group vs 6.7% in expectant management group (risk difference 5.3; 95% CI −2.2 to 12.6). Maternal and neonatal morbidity was also similar across the two groups. CONCLUSION: Manual rotation of occiput posterior positions at the start of second stage of labor does not increase the rate of vaginal delivery without instrumental assistance. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT03009435. Abstract : Manual rotation of fetuses in occiput posterior positions at the start of the second stage of labor does not increase the rate of spontaneous vaginal delivery.